Flexible polymer display technologies - Sevim, Ali Osman. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Conjugated polymers are semiconductors that have attracted increasing attention especially in the last decade, which enabled fabrication of polymer light emitting diodes (PLEDs), polymer circuits, polymer photodetectors and solar cells. They offer flexibility, simplicity and feasibility in fabrication. They lead to a technology which can monolithically integrate the devices mentioned above to micro-electromechanical systems (MEMS). Polymer photonic devices have lower performance compared to inorganic counterparts and have degradation problem. They still need fabrication refinements, more characterization, testing and product treatments for performance improvement. This research presents a novel method as a post-fabrication treatment that improves the performance of polymer light emitting diodes. Investigated PLED is made of indium tin oxide (ITO), poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS), poly[2-methoxy-5-(2'-ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) and aluminum. Fabrication process of the polymer light emitting diode is systematically evaluated. Vacuum heat treatment is performed at 130 ºC for one hour and electric field treatment is realized with negative voltages. Post fabrication heat treatment restores the light emitting function of PLEDs, which have failed due to absorbed oxygen and humidity during fabrication realized in normal room conditions. Electric field treatment lowers the turn-on voltage of PLEDs from 11 volts to 4 volts after treatment with -1 volt, when they are used as light emitting devices. Also it improves open circuit voltages and short circuit currents by an order of magnitude when they are used as photo-detectors or photocells after packaging. Electric field treatment applied after the thermal treatment also improves the uniformity of the devices.
Keywords: Light emitting diodes.; Electroluminescent devices.